Comparison of primary molar crown dimensions with two brands of stainless steel crowns in a sample of Iranian children - Mehrdad Kahvand; Mostafa Vahedian; Mansoureh Hadadzadeh; Ali Saleh; Aida Mehdipour (Tehran University of Medical Sciences, 2023)
Background and Aims: One of the concerns of dentists is selecting a suitable brand of stainless steel crowns with maximum dimensional adaptation with primary teeth. The aim of this study was to compare the primary molar crown dimensions with that of two brands of stainless steel crowns (SSCs) in a sample of Iranian children. Materials and Methods:  In this study, 130 eligible children between 3 and 12 years (66 boys, 64 girls) were selected. After recording the demographic information, the mesiodistal, buccolingual and occluso-gingival dimensions of first (D) and second (E) primary molars were measured on dental casts and compared with the dimensions of KTR (MeiMeiMinBenjing, Benjing, China) and Shinghung (Shinhungcompany, Seoul, South Korea) SSCs. Data were assessed using chi-square test and Pearson correlation coefficient. P<0.05 was considered statistically significant. Results: In this study, the most dimension matching of the teeth with that of SSCs were observed mesiodistally in upper D and lower D, buccolingualy in the upper D and lower D, and occluso-gingivaly in upper D and lower E. The most cases of mismatch in the mesiodistal dimensions of the teeth with that of SSCs were observed in the lower E and upper D. Also, the most cases of mismatch in the buccolingual dimension were found for upper E and lower E. Conclusion: Both SSCs brands in this study showed significant dimensional adaptation with the primary teeth in Iranian children. The most dimensional adaptation was between KTR SSCs and maxillary primary molars, and between Shinhung SSCs and mandibular primary molars.